Cytokinins in the in vitro multiplication and analysis of the volatile fraction of Hyptis marrubioides - Rodrigues, Mariane; Bertolucci, Suzan kelly; Alvarenga, Ivan; Silva, Sâmia; Carvalho, Alexandre; Pinto, José Eduardo (Revista Ciência Agronômica, 2018)
The aim of this study was to evaluate different concentrations of two cytokinins in the in vitro propagation of the medicinal plant Hyptis marrubioides Epl. and to analyse the volatile fraction of the compounds. Nodal segments of plants were inoculated onto Murashige and Skoog (MS) solid medium with different concentrations of benzylaminopurine (BAP) or tidiazuron (TDZ) under a 16/8 h light/dark cycle at 25 ± 2 °C. After 45 days growth, the plants were evaluated for the number and length of the shoots and for shoot dry matter. The volatile constituents were analysed by headspace-GC/MS. The greatest number of shoots was obtained with 1.0 mg L-1 TDZ in the MS medium. The greatest values for shoot length and dry matter were obtained with BAP. Twenty-seven compounds were characterised as constituents of the essential oil of H. marrubioides. The major compounds of the volatile fraction were sabinene, α-thujone, β- thujone, α-copaene, β-caryophyllene, γ-gurjunene and γ-himachalene. The types and concentrations of the growth regulators influenced accumulation of the volatile fraction. Quantitative changes in the monoterpenes and sesquiterpenes in the volatile fraction of the plants were also seen in response to the type of growth regulator added to the culture medium.